The Role of the Negative Regulation of Microglia-Mediated Neuroinflammation in Improving Emotional Behavior After Epileptic Seizures - Wu, Qiong; Wang, Hua; Liu, Xueyan; Zhao, Yajuan; Zhang, Junmei (Frontiers in Neurology, 2022)
Objective Studies have long shown that uncontrolled inflammatory responses in the brain play a key role in epilepsy pathogenesis. Microglias play an important role in epileptic-induced neuroinflammation, but their role after epileptic seizures is still poorly understood. Alleviating epilepsy and its comorbidities has become a key area of interest for pediatricians. Methods A pilocarpine-induced rat model of epilepsy was established. The rats were randomly divided into four groups: a control group, epilepsy group, TLR4 inhibitor group (epilepsy+TAK-242), and NF-κB antagonist group (epilepsy+BAY11–7082). Results 1. The results of TUNEL staining showed that the expression in rats in the epilepsy group was the most obvious and was significantly different from that in rats in the control, EP+BAY and EP+TAK groups. 2. The expression of TLR4 and NF-κB was highest in rats in the epilepsy group and was significantly different from that in rats in the control, EP+BAY and EP+TAK groups. 3. The fluorescence intensity and number of IBA-1-positive cells in rats in the epilepsy group were highest and significantly different from those in rats in the control, EP+BAY and EP+TAK groups. Western blot analysis of IBA-1 showed that the expression in rats in the epilepsy group was the highest and was statistically significant. 4. CD68 was the highest in rats in the epilepsy group and was statistically significant. 5. In the open-field experiment, the central region residence time of rats in the EP group was delayed, the central region movement distance traveled was prolonged, the total distance traveled was prolonged, and the average speed was increased. Compared with rats in the EP group, rats in the EP+BAY and EP+ TAK groups exhibited improvements to different degrees. Conclusion At the tissue level, downregulation of the TLR4/NF-κB inflammatory pathway in epilepsy could inhibit microglial activation and the expression of the inflammatory factor CD68, could inhibit hyperphagocytosis, and inhibit the occurrence and exacerbation of epilepsy, thus improving cognitive and emotional disorders after epileptic seizures.